Ginsenoside Rg3 Promotes Cell Growth Through Activation of mTORC1 - Liu, Wei; Zhang, Sheng-Xiong; Ai, Bo; Pan, Hua-Feng; Zhang, Dan; Jiang, Yu; Hu, Lei-Hao; Sun, Ling-Ling; Chen, Zhe-Sheng; Lin, Li-Zhu (Frontiers in Cell and Developmental Biology, 2021)
Ginsenoside Rg3 is a steroidal saponin isolated from Panax ginseng. Previous studies have shown that Rg3 treatment downregulates the activity of rapamycin complex 1 (mTORC1) activity and inhibits the growth of cancer cells. However, the inhibitory effect of Rg3 on cancer cells is associated with high concentrations of Rg3 that are difficult to achieve in vivo. The human cervix adenocarcinoma HeLa cells were treated with Rg3. The protein levels of AMP-activated protein kinase alpha (AMPKα), protein kinase B(Akt), ribosomal S6 protein(S6), and Erk were determined by immunoblotting analyses. We used a fluorescent probe to detect reactive oxygen species (ROS) production in living cells. The oxygen consumption rate was examined by the Seahorse. Extracellular Flux Analyzer. The content of ATP was measured by ATPlite kit and Mitotracker was applied to detect the mitochondria. We showed that at lower concentrations, Rg3 activates mTORC1 independent of AKT and AMPK. Rg3 promotes mitochondrial biogenesis and function, increases the oxygen consumption of mitochondria and the content of ATP. This effect is in contrast to that of high concentrations of Rg3, which inhibits cell growth. These findings demonstrate a pro-growth activity of Rg3 that acts through mTORC1 and mitochondrial biogenesis and suggest a dose-dependent effect of Rg3 on tumor cell growth.